RANCANG BANGUN MODEL SISTEM CONTROLLING DAN OTOMATISASI ROBOT PENGANGKUT SAMPAH DALAM RUANGAN - Riki Ruli A. Siregar; Suyanto Suyanto (Sekolah Tinggi Teknik - PLN, 2015)
Trash has been a serious problem. All this time, people is used to just throw away theirgarbage to garbage cans and leave the res of the process to instances that are responsible fortaking care the daily waste of human's lives. In real life, garbage problems extend to the point ofhealth and environment issues. Garbage also affects the cleanliness of a room, in which the morehousehold consumption the more garbage is being created. The purpose of this writing is to designa controlling system model and a garbage robot automation. The result of this design is expected tohelp humans to carry their garbage out of their rooms.